Genotype Variation for Phosphorus Uptake and Use Efficiency in Triticale on Calcareous Soil - GULMEZOGLU ATILGAN, NURDILEK; HELVACI, DERYA (Asian Journal of Chemistry, 2010)
11 Winter triticale genotypes (5 lines and 6 released varieties) were evaluated and classified using Metroglyph analysis according to their grain yield performance and phosphorus uptake under both dryland and calcareous soil condition in Turkey. All genotypes were grown at a single rate of P (26 kg/ha). The grain yield of the lines and the combined genotypes were found to be significant (p < 0.05). TVD-17 in particular was found to have had the highest total P-uptake (15.62 %) and grain yield (3912 kg/ha). The grain yield, biological yield, P content in grain (%) and total P-uptake (%) averages of the lines were higher than that of the varieties. The results revealed that while TVD-17 appeared in the HGYHP (high grain yield-high P-uptake) group, Tatlicak 97 variety was in the LGY-LP (low grain yield-low P-uptake) group.